JULIO C. TELLO AND PERUVIAN ARCHEOLOGY ILLUSTRATION - Echevarría López, Gori Tumi (2012)
This essay covers a little-studied facet of the career and professional development of Dr. Julio C. Tello Rojas, the father of Peruvian archaeology and one of the most conspicuous and important archaeologists of America. For its purpose the author examines the state of the art of the anthropologic and archeological illustration in Peru before the accession of Julio C. Tello in the national archaeological studies, evaluating from here the proposal, emergence and development of a school of graphic illustration, formed and directed by this Peruvian intellectual. The author concludes that the school of Peruvian archaeological illustration is an outstanding contribution of Julio C. Tello to Peru’s archaeology and history of art.